Penyuluhan Tentang Pencegahan Stunting Pada Remaja Di SMK N 1 Batang Toru - Tajuddi Siregar; Ritonga, Nefonavratilova (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2023)
Stunting is a nutritional problem that threatens the quality of life of the nation's future generations. The complexity of the stunting problem, which is a link in the chain, starts from parents' initial education regarding the importance of knowledge about stunting. The importance of knowledge about stunting from adolescence in order to prevent the birth of babies with nutritional problems which cause the growth of toddlers with stunting. Education about the stunting rate in Aek Ngadol Village, Batang Toru District and the absence of socialization by health workers regarding the prevention of stunting from adolescence. In this socialization, an assessment of knowledge about stunting was carried out using the counseling method for students, outreach activities and discussion of material regarding stunting and the first 1000 days of life in adolescents, as well as an assessment of students' knowledge after the counseling was carried out with a question and answer session regarding the material presented. The results of this activity providing questions and answers showed that there had been an increase in students' knowledge about stunting and the first 1000 days of life. Seeing the enthusiasm of students and the importance of efforts to prevent stunting from adolescence with education about stunting and the first 1000 days of life and it is recommended that this outreach be carried out by health workers from local health service facilities periodically to all students so that it can reach all teenagers in Aek Ngadol Village, District Batang Toru, South Tapanuli Regency. Keywords : Education, Demonstration, Stunting